using induction, prove that 10n + 3.4n+2 + 5 is divisible by 9
Answers
Answered by
1
☆☆ranshsangwan☆☆
For n = 0, we have:
10^n + 3 * 4^(n + 2) + 5
= 10^0 + 3 * 4^(0 + 2) + 5
= 54
which is divisible by 9. Thus, it works at least for n = 0. Suppose it works for some n = k .That is, the expression:
10^k + 3 * 4^(k + 2) + 5
is divisible by 9, i.e. there exists some M such that:
10^k + 3 * 4^(k + 2) + 5 = 9M
Then, consider the n = k + 1 case:
10^(k + 1) + 3 * 4^(k + 3) + 5
= 10 * 10^k + 12 * 4^(k + 2) + 5
We need to find the expression 10^k + 3 * 4^(k + 2) + 5 in there. This is always the hardest part of these proofs. Basically, what happens is we choose one of these terms and try to pull out as many copies of 10^k + 3 * 4^(k + 2) + 5 out of it as possible. I'm going to pick the 12 * 4^(k + 2) term. There are 4 copies of the 3 * 4^(k + 3) term in there, so lets pull out 4 copies of 10^k + 3 * 4^(k + 2) + 5 from the entire expression:
10 * 10^k + 12 * 4^(k + 2) + 5
= 4 * 10^k + 4 * 3 * 4^(k + 2) + 4 * 5 + 6 * 10^k - 15
= 4 * (10^k + 3 * 4^(k + 2) + 5) + 6 * 10^k - 15
= 4 * 9M + 6 * 10^k - 15
Notice now that 4 * 9M is divisible by 9. We just need to show 6 * 10^k - 15 is divisible by 9. We can take out a factor of 3, and we can therefore see that we need to show that:
2 * 10^k - 5
is divisible by 3 for k >= 0. If k = 0, then it certainly is divisible by 3. If k > 0, then:
2 * 10^k - 5
= 20 * 10^(k - 1) - 5
= 5(4 * 10^(k - 1) - 1)
Now, notice that:
10 = 1 (mod 3)
===> 10^(k - 1) = 1^(k - 1) = 1 (mod 3)
===> 4 * 10^(k - 1) - 1 = 4 * 1 - 1 = 3 = 0 (mod 3)
===> 5 * (4 * 10^(k - 1) - 1) = 5 * 0 = 0 (mod 3)
If you don't like modulo arithmetic, the above can be proven by a separate induction argument. Thus 2 * 10^k - 5 is divisible by 3, as we needed. Therefore:
10^(k + 1) + 3 * 4^(k + 3) + 5 = 4 * 9M + 6 * 10^k - 15
is divisible by 9, and so 10^n + 3 * 4^(n + 2) + 5 is divisible by 9 for all n.
For n = 0, we have:
10^n + 3 * 4^(n + 2) + 5
= 10^0 + 3 * 4^(0 + 2) + 5
= 54
which is divisible by 9. Thus, it works at least for n = 0. Suppose it works for some n = k .That is, the expression:
10^k + 3 * 4^(k + 2) + 5
is divisible by 9, i.e. there exists some M such that:
10^k + 3 * 4^(k + 2) + 5 = 9M
Then, consider the n = k + 1 case:
10^(k + 1) + 3 * 4^(k + 3) + 5
= 10 * 10^k + 12 * 4^(k + 2) + 5
We need to find the expression 10^k + 3 * 4^(k + 2) + 5 in there. This is always the hardest part of these proofs. Basically, what happens is we choose one of these terms and try to pull out as many copies of 10^k + 3 * 4^(k + 2) + 5 out of it as possible. I'm going to pick the 12 * 4^(k + 2) term. There are 4 copies of the 3 * 4^(k + 3) term in there, so lets pull out 4 copies of 10^k + 3 * 4^(k + 2) + 5 from the entire expression:
10 * 10^k + 12 * 4^(k + 2) + 5
= 4 * 10^k + 4 * 3 * 4^(k + 2) + 4 * 5 + 6 * 10^k - 15
= 4 * (10^k + 3 * 4^(k + 2) + 5) + 6 * 10^k - 15
= 4 * 9M + 6 * 10^k - 15
Notice now that 4 * 9M is divisible by 9. We just need to show 6 * 10^k - 15 is divisible by 9. We can take out a factor of 3, and we can therefore see that we need to show that:
2 * 10^k - 5
is divisible by 3 for k >= 0. If k = 0, then it certainly is divisible by 3. If k > 0, then:
2 * 10^k - 5
= 20 * 10^(k - 1) - 5
= 5(4 * 10^(k - 1) - 1)
Now, notice that:
10 = 1 (mod 3)
===> 10^(k - 1) = 1^(k - 1) = 1 (mod 3)
===> 4 * 10^(k - 1) - 1 = 4 * 1 - 1 = 3 = 0 (mod 3)
===> 5 * (4 * 10^(k - 1) - 1) = 5 * 0 = 0 (mod 3)
If you don't like modulo arithmetic, the above can be proven by a separate induction argument. Thus 2 * 10^k - 5 is divisible by 3, as we needed. Therefore:
10^(k + 1) + 3 * 4^(k + 3) + 5 = 4 * 9M + 6 * 10^k - 15
is divisible by 9, and so 10^n + 3 * 4^(n + 2) + 5 is divisible by 9 for all n.
Similar questions